Offshore platforms for sustainable development of ocean resources.
Europe's coastal areas are becoming more crowded and space for developing marine renewable energy and other environment-friendly technologies is limited. Floating offshore platforms capable of supporting a range of sustainable, eco-friendly activities could be the answer we are all looking for.